2018
DOI: 10.1371/journal.pone.0194449
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and biological activity in young sesame leaves (Sesamum indicum L.) and changes in iridoid and polyphenol content at different growth stages

Abstract: Three iridoids (lamalbid (I1), sesamoside (I2) and shanzhiside methyl ester (I3)) and seven polyphenols (cistanoside F (P1), chlorogenic acid (P2), pedalitin-6-O-laminaribioside (P3), pedaliin (P4), isoacteoside (P6), pedalitin (P7) and martynoside (P8)) were identified in young sesame leaves (Sesamum indicum L.) other than the acteoside (P5) reported previously. P3 was a new compound, and I1, I3, P2 and P8 were found in a species of Sesamum for the first time. HPLC analyses revealed that the compounds I1 (0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
(42 reference statements)
1
30
0
1
Order By: Relevance
“…These three compounds are position isomers with two catechol units, one from each part connected to the glycosidic portion which are equal to hydroxytyrosol and caffeic acid (Figure 5B). Some authors have reported the higher antioxidant activity of verbascoside than that of isoverbascoside, reflecting the influence of the caffeoyl moiety position [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…These three compounds are position isomers with two catechol units, one from each part connected to the glycosidic portion which are equal to hydroxytyrosol and caffeic acid (Figure 5B). Some authors have reported the higher antioxidant activity of verbascoside than that of isoverbascoside, reflecting the influence of the caffeoyl moiety position [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…× 250 mm, particle size 5 μm; Nomura Chemical, Tokyo, Japan) column at 45˚C and a flow rate of 1.0 mL/min with 20% acetonitrile as the mobile phase to afford pedaliin (6.0 mg). Prepared pedaliin was completely characterized by spectral analysis and comparison with reported data [13]. H-qNMR measurement and calculation of the purity of each sample.…”
Section: Isolation Of Pedaliinmentioning
confidence: 99%
“…In previous studies, our group chemically characterized three iridoids and eight polyphenols in young sesame leaves (Sesamum indicum L.), including their biological activities such as 1,1-diphenyl-2-picrylhydrazyl radical scavenging, oxygen radical absorbance capacity, in vitro antiglycation activity, changes in the content of five compounds at each growth stage of sesame leaves, and the accumulation and subcellular localization of acteoside (verbascoside) in sesame plants [12][13][14]. Among the polyphenols identified, acteoside and pedaliin (pedalitin-6-O-glucoside) are respectively a major phenylethanol glycoside and a flavonoid glycoside in young sesame leaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phenolic compounds can be extracted with acetone from Guayusa leaves [ 25 ]. A total of three iridoids and seven polyphends were identified in sesame leaves by ethanol extraction [ 26 ]. Quinic acid was identified in Marula leaves by ethanol extraction [ 27 ].…”
Section: Introductionmentioning
confidence: 99%